What is the comparative effectiveness of standard supportive care versus fluid replacement therapy in reducing mortality for children with dengue hemorrhagic fever? : A Systematic Review - Andrian Dwi Rizki Setyawan; Edy sucipto (The International Journal of Medical Science and Health Research, 2025)
Introduction: Dengue Hemorrhagic Fever (DHF) is a severe complication of dengue infection in children, where fluid management is a critical but controversial component of care. The optimal strategy for fluid replacement remains debated, with risks associated with both under- and over-resuscitation. This systematic review aims to evaluate the comparative effectiveness of various fluid replacement therapies versus standard supportive care in reducing mortality for children with DHF. Methods: A systematic review was conducted following PRISMA 2020 guidelines. Searches were performed in PubMed, Springer, Semantic Scholar, Google Scholar, and Wiley Online Library. Inclusion criteria focused on studies of pediatric patients (≤18 years) with confirmed DHF, comparing fluid replacement therapies with standard care, and reporting mortality as an outcome. After screening, 11 studies, including randomized controlled trials and observational studies, were included in the narrative synthesis. Results: The findings were highly conflicting and context-dependent. In resource-limited African settings, studies found that aggressive fluid boluses were associated with significantly higher mortality compared to maintenance-only fluid strategies. Conversely, studies in intensive care units (ICUs) demonstrated that restrictive fluid strategies or targeted interventions (e.g., early albumin, advanced monitoring) significantly reduced mortality compared to liberal or standard therapy. Furthermore, improved physician adherence to WHO guidelines also led to decreased mortality. Discussion: The evidence indicates there is no single superior fluid management strategy for all children with DHF. The optimal approach is critically dependent on the clinical setting and available resources. The stark contrast between the harm caused by bolus fluids in low-resource settings and the benefits of advanced, targeted care in high-resource ICUs suggests that global, one-size-fits-all guidelines may be inappropriate. Conclusion: Studies promoting minimal intervention or restrictive maintenance fluid protocols demonstrated either comparable or superior outcomes, with fewer complications and a reduced burden on the healthcare system. Conversely, in well-equipped intensive care units, highly structured and targeted interventions, which may include early colloid administration and vigilant monitoring for complications like abdominal compartment syndrome, have been shown to drastically reduce mortality.